(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
This article aims to shed some light on how niqabi women in Spain present and define themselves according to the meaning they attach to the niqab. In addition, a specific objective of the study was to find out how these women articulate, formulate and explain the niqab. For the purpose of the study, we interviewed twelve women. The only common requirement for being part of the sample was to be a niqabi living in Spain. We therefore decided to use non-probability sampling. At the same time, we employed the «snowball» sampling technique whereby the sample was contacted in two specific ways: through different Internet social media and using key informants to recruit participants for the face-to-face interviews. The interviews focused on two very specific questions: what meaning do the women attach to the niqab and what are their political, religious and social motivations for wearing it. The research findings point to growing support for the niqab and Muslim women are increasingly being encouraged to wear it.